Magnetic Hysteresis at 10 K in Single Molecule Magnet Self‐Assembled on Gold. Issue 5 (21st January 2021) - Chen, Chia‐Hsiang; Spree, Lukas; Koutsouflakis, Emmanouil; Krylov, Denis S.; Liu, Fupin; Brandenburg, Ariane; Velkos, Georgios; Schimmel, Sebastian; Avdoshenko, Stanislav M.; Fedorov, Alexander; Weschke, Eugen; Choueikani, Fadi; et al.
Abstract: Tremendous progress in the development of single molecule magnets (SMMs) raises the question of their device integration. On this route, understanding the properties of low‐dimensional assemblies of SMMs, in particular in contact with electrodes, is a necessary but difficult step. Here, it is shown that fullerene SMM self‐assembled on metal substrate from solution retains magnetic hysteresis up to 10 K. Fullerene‐SMM DySc2 N@C80 and Dy2 ScN@C80 are derivatized to introduce a thioacetate group, which is used to graft SMMs on gold. Magnetic properties of grafted SMMs are studied by X‐ray magnetic circular dichroism and compared to the films of nonderivatized fullerenes prepared by sublimation. In self‐assembled films, the magnetic moments of the Dy ions are preferentially aligned parallel to the surface, which is different from the disordered orientation of endohedral clusters in nonfunctionalized fullerenes. Whereas chemical derivatization reduces the blocking temperature of magnetization and narrows the hysteresis of Dy2 ScN@C80, for DySc2 N@C80 equally broad hysteresis is observed as in the fullerene multilayer. Magnetic bistability in the DySc2 N@C80 grafted on gold is sustained up to 10 K. This study demonstrates that self‐assembly of fullerene‐SMM derivatives offers a facile solution‐based procedure for the preparation of functional magnetic sub‐monolayers with excellent SMM performance. Abstract : Fullerene single molecule magnets DySc2 N@C80 and Dy2 ScN@C80 are derivatized with thioacetate linker groups and assembled as monolayers on the Au(111) substrate. Magnetic properties of the self‐assembled monolayers are studied by X‐ray magnetic circular dichroism. The molecules retain their magnetic hysteresis on gold, which for DySc2 N@C80 is observed up to 10 K.